2015
DOI: 10.1590/0103-6440201300022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Passive Ultrasonic Irrigation on Enterococcus faecalis from Root Canals: An Ex Vivo Study

Abstract: Endodontic irrigation aims to clean and disinfect the root canal system. Passive ultrasonic irrigation (PUI) is based on the use of an ultrasound-activated instrument into the root canal filled with irrigant. The aim of this study was to evaluate, ex vivo, the effectiveness of PUI in eliminating Enterococcus faecalis from root canals. Seventy-five extracted human single-root teeth were used. After root canal preparation, specimens were inoculated with E. faecalis and incubated at 37 °C for 21 days. Specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 24 publications
1
31
1
8
Order By: Relevance
“…Enhanced ATP assay kit can be used to detect the levels of ATP in common solutions, and different cells or tissues. Previous studies used paper points for sampling of bacteria from contaminated root canals (Guerreiro‐Tanomaru, Chavez‐Andrade, de Faria‐Junior, Watanabe, & Tanomaru‐Filho, ). Our study revealed no significant differences among the six subgroups in the CNI or LAI group after irrigation, and significantly greater reduction of ATP level in LAI than that in CNI ( p < .05), which is consistent with the results of a recent study that reported no significant differences in CFU value between the 3% NaOCl and CHX groups (Zhu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced ATP assay kit can be used to detect the levels of ATP in common solutions, and different cells or tissues. Previous studies used paper points for sampling of bacteria from contaminated root canals (Guerreiro‐Tanomaru, Chavez‐Andrade, de Faria‐Junior, Watanabe, & Tanomaru‐Filho, ). Our study revealed no significant differences among the six subgroups in the CNI or LAI group after irrigation, and significantly greater reduction of ATP level in LAI than that in CNI ( p < .05), which is consistent with the results of a recent study that reported no significant differences in CFU value between the 3% NaOCl and CHX groups (Zhu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The plate culture method was used in this study because of its simplicity and efficiency (5,7,(8)(9)(10)(11)(13)(14)(15)(16)(17)(18)(19). Molecular methods has been highlighted because of their high sensibility to detect microorganisms, but such a feature would not be necessary in this study as there was no total absence of bacterial growth in the collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that the endodontic treatment is performed in association with chemical substances, which are aimed to assist instrumentation and enhance disinfection (5,13,15,22). Previous studies (17,22) observed that chemical substances used as irrigant have antimicrobial activity and reduce the bacterial number in the root canal, while other authors (23) confirmed that sodium hypochlorite penetrates into dentinal tubules, and found that bacteria on root canal surface and dentinal tubules were significantly reduced when the antimicrobial agents were used (18). Moreover, bacterial remaining was found at S2 and S3 collection, the chemical substances could reduce the bacterial amount.…”
Section: Discussionmentioning
confidence: 99%
“…The impact caused by the phenomenon promotes smear layer removal, mainly in the areas where instruments cannot reach (19)(20)(21). Thus, it is valid to state that the same phenomenon may occur with the filling material (19,20).…”
Section: Discussionmentioning
confidence: 99%